Influence of Supply Chain Integration, Information Sharing, and Supplier Relationships on Operational Efficiency of Manufacturing Companies - Prananta, Arie Wahyu; Hidayat, Khoirul (IJBLE Scientific Publications Community Inc., 2024)
This research investigates the influence of supply chain integration, information sharing, and supplier relationships on operational efficiency in manufacturing companies across diverse industries. A quantitative research approach is employed, utilizing surveys to collect data from 300 organizations. Correlation analysis, regression analysis, mediation analysis, moderation analysis, and structural equation modeling are utilized to analyze the data and test hypotheses. The results demonstrate significant positive correlations between supply chain integration, information sharing, supplier relationships, and operational efficiency. Regression analysis confirms the significant impact of these dimensions on operational efficiency, with supply chain integration exhibiting the strongest effect. Mediation analysis reveals that information sharing and supplier relationships partially mediate the relationship between supply chain integration and operational efficiency. Moreover, the moderation analysis highlights industry sector as a significant moderating factor. The findings underscore the strategic importance of supply chain integration, information sharing, and supplier relationships in driving operational excellence and offer actionable insights for supply chain management practitioners.